2007
DOI: 10.1097/sle.0b013e3180dc93aa
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Iatrogenic Splenectomy During Open and Laparoscopic Colon Resection

Abstract: Iatrogenic splenic injury requiring splenectomy is a well-recognized and potentially serious complication of colon resection. Iatrogenic splenectomy is associated with significant morbidity and mortality, including bleeding and the postsplenectomy sepsis syndrome. Our study aims to compare the incidence of iatrogenic splenectomy in laparoscopic colon resection with that of open colon resection over an 11-year-period at Mount Sinai. A retrospective chart review of all patients undergoing colon resection at Moun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 10 publications
0
17
2
Order By: Relevance
“…One intraoperative complication of splenic injury requiring splenectomy occurred in the open STC group. While not statistically significant, available literature does support decreased iatrogenic splenic injury with laparoscopic versus open colectomy [21].…”
Section: Discussionmentioning
confidence: 97%
“…One intraoperative complication of splenic injury requiring splenectomy occurred in the open STC group. While not statistically significant, available literature does support decreased iatrogenic splenic injury with laparoscopic versus open colectomy [21].…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the etiology of surgical spleen injuries (type of procedures and surgeries), it was found evidencesuggesting prevalence of 0.5 % in upper tract urological laparoscopic surgery, recognized intraoperative in 85.7 % (Evidence level type 4) (Chung et al, 2011); left nephrectomy 4.0 to 14.5 % (Evidence level type 4) (Cassar & Munro, 2009;Coon, 1990;Tan et al, 2011); during elective left hemicolectomy in 0.24 % to 8.0 % (Evidence level type 4) (Coon, 1990;Malek et al, 2007;Holubar et al, 2009;Cassar & Munro, 2009;Merchea 2012;Masoomi et al, 2012); during antireflux surgery in 2.0 to 20 %, depending on characteristics of patients (Evidence level type 4) (Coon, 1990;Urschel, 1993;Flum et al, 2001;Cassar & Munro, 2009); during abdominal vascular surgery 21.0 to 60.0 % (Evidence level type 4) (Eaton et al, 2000;Cassar & Munro, 2009;Coon, 1990); in the course of surgery for gastric and duodenal ulcers injuries of the spleen were found in 1.4 % of patients (Evidence level type 4) (Nikolaev et al, 1990); as a complication of upper gastrointestinal endoscopy, ERCP and colonoscopy (Evidence level type 3a and 4) (Piccolo et al, 2014;Ong et al, 1991;Kamath et al, 2009;Ha & Minchin, 2009;Paredes et al, 2013); in the course of laparoscopic cholecystectomy (Evidence level type 4) (Bracale et al, 2013;Geraci et al, 2014); as a complication of bariatric surgery, were found in 0.21 % of patients (Evidence level type 5) (American Society for Metabolic & Bariatric Surgery, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-nine articles in extensive were discarded for failing to meet the eligibility criteria. Finally, the population in study consisted of 35 articles, 3 of evidence level type 3a (Renzulli et al, 2009;He et al, 2014;Piccolo et al, 2014), 32 of evidence level type 4 (Bagrodia et al, 2014;Barmparas et al, 2015;Bracale et al, 2013;Cassar & Munro, 2009;Coon, 1990;Chung et al, 2011;Davies et al, 2014;Eaton et al, 2000;Eber et al, 1999;Edgren et al, 2014;Flum et al, 2001;Geraci et al, 2014;GĂłmez Alonso et al, 2001;Ha & Minchin, 2009;Harbrecht et al, 2008;Holubar et al, 2009;Kamath et al, 2009;Malek et al, 2007;Masoomi et al, 2012;McIntyre et al, 2005;Merchea et al, 2012;Nikolaev et al, 1990;Ong et al, 1991;Paredes et al, 2013;Rogers et al, 1980;Singla, et al, 2012;Tan et al, 2011;Urschel, 1993;Wang et al, 2011;Yong et al, 2010; and 1 of evidence level type 5 (American Society for Metabolic & Bariatric Surgery, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In our series, the number of laparoscopic cases was small and therefore it would be difficult to draw any definitive conclusions. Interestingly, Malek et al [26] reviewed incidence of iatrogenic injury during open and laparoscopic colon resection and reported a significant difference (p = 0.03) in the incidence of iatrogenic splenectomy (open 13/5,477; laparoscopic 0/1,911). Only 29 left nephrectomies were performed laparoscopically in our series and therefore a meaningful comparison is implausible.…”
Section: Discussionmentioning
confidence: 99%